Tension pneumoperitoneum in a child as complication of high frequency oscillatory ventilation: A case report - Mounika V Reddy; Arun Baranwal; Muralidharan Jayashree (Wolters Kluwer Medknow Publications, 2019)
Pneumoperitoneum is most often secondary to a perforated hollow viscous mandating urgent surgical intervention. Pneumoperitoneum as a life-threatening complication of mechanical ventilation is rarely reported and presents a diagnostic and therapeutic challenge. Here, we report an 18-month old boy who developed tension pneumoperitoneum and abdominal compartment syndrome as complication of high frequency oscillatory ventilation, and was managed with percutaneous needle paracentesis. Awareness and thus early recognition of this rare complication of mechanical ventilation may help avoid needless laparotomy, and its associated morbidity.